PENGARUH INTENSITAS PENEBANGAN DAN LERENG TERHADAP KETERBUKAAN TANAH - Jurnalis Thaib (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
Ground exposure is one of the stand damages caused by logging. Logging which generally do not comply with the stipulation of the Indonesian Selective Cutting (TPI) system, have caused varying degrees of ground exposure as follows:On slopes of 0 - 25% where the number of trees felled per hectare are 0 - 4,5 - 9 and 10 or up, ground exposure varied between 5.4 -13.8%, 13.4 - 22.5%, and 20.9 - 26.6% respectively.On slopes of 26% and up, where the number of trees felled per hectare are 0 - 4, 5 - 9 and 10 or up, ground exposure varied between 7.6 - 13.8%, 11.9 - 19.7% and 17.1- 24.6% respectively.Dominant factors in the process of ground exposure are management, particularly with regard to the organization of skidding and hauling activities, and the number of trees felled per unit area. Unproductive tractor movements e.g. in locating logs, increases ground exposures and total cost per unit logs produced, and should therefore be avoided.